Ecological and physiological implications of rehabilitation and reintroduction of woolly monkeys genus Lagothrix in Vichada, Eastern Colombia. (2018)
Large primates are of vital importance for tropical rainforest ecosystems. It is well established that woolly monkeys (Lagothrix lagothricha) are very important seed dispersers, maintaining plant diversity in South American forests. According to IUCN, all subspecies of woolly monkeys are threatened to some extent, the Colombian woolly monkey being the most endangered (L. l. lugens classed as critically endangered - CR). Actually, they have been considered locally extinct in large parts of their original distribution. These primates are not only threatened by deforestation and habitat loss but also by subsistence hunting and illegal wild life trade, resulting in a large number of woolly monkeys in rescue centres and zoos. This project has three main objectives: 1) to rehabilitate and release a group of woolly monkeys that were kept in captivity, 2) to monitor the effect of these primates on ecosystem functioning after the reintroduction process and 3) to evaluate how the hormones level (glucocorticoids and testosterone), and parasite loads can change during the process of rehabilitation and the reintroduction into the wild. First, an assessment of the quality of the release site will be performed in terms of plant composition (both adult trees and regenerating plants), fruit production, and local mammal communities. During the monkeys' rehabilitation both social and ecological behaviour will be quantified using focal animal sampling, to determine release viability for each one of the individuals in the colony. Moreover, fecal samples will be collected to determine baseline hormone levels before the reintroduction program. The reintroduced group will be monitored in the first year by telemetry and GPS systems. In addition, we will evaluate changes in behavior, group size and composition. When a group gets established we will test the potential effects of inter-specific competition on two other primate species. For this purpose we will conduct line transect censuses (4 km long). Weekly, during the establishment of groups and for a year after the reintroduction, we will collect fecal samples to determine how the woolly monkeys respond physiologically to the reintroduction and to evaluate how inter- and intra-group competition can drive hormonal changes. Finally, we will compare the establishment of seedlings before and after the release of woolly monkeys in order to monitor their effect on plant communities (using 75 4-m2 vegetation plots within the range of the monkeys and in control sites). Since woolly monkeys have been described as effective seed dispersers, we expect that the diversity of seedling will increase in their core home range areas. This will be the first reintroduction project aiming to make detailed quantification of the effect of monkeys on the habitat, in terms of competition with local primates and the diversity of regenerating plants.